Incoherent broadband mid-infrared detection with lanthanide nanotransducers - Liang, Liangliang (2022)
Spectral conversion of mid-infrared (MIR) radiation to visible (VIS) and near-infrared (NIR) wavelengths is a fundamental technology for spectroscopy and imaging; however, current MIR-to-VIS/NIR conversion technology is limited to nonlinear optics with bulky crystals or resonant nanocavities. Here we report lanthanide-based MIR-to-NIR nanotransducers that enable broadband MIR sensing at room temperature by harnessing ratiometric luminescence changes. The ratiometric luminescence of lanthanide nanotransducers in the NIR region can be incoherently modulated by MIR radiation in the 4.5–10.8 µm wavelength range. Ratiometric modulation of luminescence enables a detection limit of ~0.3 nW × µm−2 with an internal quantum efficiency on the order of 3 × 10−3. The ratiometric sensor based on lanthanide nanotransducers does not require cryogenic cooling, polarization control, phase matching or nanoantenna design for light confinement. We also developed a camera with lanthanide nanotransducers, which enable room-temperature MIR imaging. We anticipate that these lanthanide nanotransducers can be extended to MIR light manipulation at the microscale for chip-integrated device applications.